Incidence, Burden, and Trend of Cutaneous Leishmaniasis over Four Decades in Iran - Bakhtiar PIROOZI; Ghobad MORADI; Cyrus ALINIA; Parvin MOHAMADI; Mohammad Mehdi GOUYA; Mahmood NABAVI; Faranak GHARACHORLOO; Mohammad Bagher KHADEM ERFAN; Mohammad Reza SHIRZADI (Tehran University of Medical Sciences, 2019)
Background: Iran is among the first six countries in the world with the highest annual incidence of cutaneous leishmaniasis. This study aimed at estimating the incidence, burden, and trend of cutaneous leishmaniasis at the national level in Iran from 1977 to 2015. Methods: This study was conducted in 2017, used Disability Adjusted Life Years (DALYs) index, recommended by the WHO for assessing the Global Burden of Diseases, to estimate the burden of cutaneous leishmaniasis. The data on the incidence of the disease and the number of cases was obtained from the communicable diseases surveillance system (Center for Communicable Diseases Control (CCDC), Ministry of Health and Medical Education (MOHME) of Iran) that routinely collects data from all over the country; in addition, some data was extracted by reviewing the texts. Considering the views expressed in a panel of experts, to calculate the actual incidence of the disease, the number of registered cases was multiplied by 5. Results: The incidence of cutaneous leishmaniasis varied from approximately 50 to 250 cases per 100,000 population during the studied period. During these years, the incidence of the disease was higher in males than females. Moreover, the burden of cutaneous leishmaniasis varied between 1.18 and 5.7 DALYs per 100000 population during the studied period. The incidence and burden of cutaneous leishmaniasis have not significantly decreased in recent years. Conclusion: Despite the implementation of a program for controlling cutaneous leishmaniasis in Iran since 1977, the incidence and burden of the disease are still high in the country; it is seriously alarming for policy makers and managers of the health system in Iran, indicating the presence of some problems in controlling the disease.